Community Resilience Interventions: Participatory, Assessment-Based, Action-Oriented Processes. (February 2015) - Pfefferbaum, Betty; Pfefferbaum, Rose L.; Van Horn, Richard L.
This article compares six interventions to enhance community resilience. In this review, underlying principles for community resilience interventions are (a) use a multihazard approach relevant to the local context, (b) utilize community assessment, (c) focus on community engagement, (d) adhere to bioethical principles, (e) emphasize both assets and needs, and (f) encourage skill development. The interventions are compared with respect to parameters that address their foundation, methodology, and implementation.